Beau travail - Tarnmoor, Salvator R. 1819-1891; Zur, Eran 1965- (<<The>> Criterion collection, 2020)
"With her ravishingly sensual take on Herman Melville’s Billy Budd, Sailor, Claire Denis firmly established herself as one of the great visual tone poets of our time. Amid the azure waters and sunbaked desert landscapes of Djibouti, a French Foreign Legion sergeant (Denis Lavant) sows the seeds of his own ruin as his obsession with a striking young recruit (Grégoire Colin) plays out to the thunderous, operatic strains of Benjamin Britten. Denis and cinematographer Agnès Godard fold military and masculine codes of honor, colonialism’s legacy, destructive jealousy, and repressed desire into shimmering, hypnotic images that ultimately explode in one of the most startling and unforgettable endings in all of modern cinema." [criterion.com]
Original: Frankreich 1999
director-approved special edition features: new 4K digital restoration, supervised by director of photography Agnès Godard and approved by director Claire Denis, with uncompressed stereo soundtrack ; new conversation between Denis and filmmaker Barry Jenkins ; new selected-scene commentary with Godard ; new interviews with actors Denis Lavant and Grégoire Colin ; new video essay by film scholar Judith Mayne ; new english subtitle translation ; plus: an essay by critic Girish Shambu
Bildformat 1.66:1
Keywords: Film; Blu-Ray-Disc